2010
DOI: 10.1089/acm.2009.0531
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Nature Scenery and Sounds Versus Urban Scenery and Sounds to Reduce Pain in Adults Undergoing Bone Marrow Aspirate and Biopsy

Abstract: We confirmed earlier findings showing that BMAB is poorly tolerated. While mean pain scores were not significantly different between the study arms, secondary analyses suggest that viewing a nature scene while listening to nature sounds is a safe, inexpensive method that may reduce pain during BMAB. This approach should be considered to alleviate pain during invasive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 26 publications
(29 reference statements)
0
44
0
7
Order By: Relevance
“…These are precisely the features that characterise natural surroundings. Earlier studies have shown a link between natural surroundings and the reduction of stress (Ulrich et al, 1991), recovery from surgical interventions (Ulrich, 1984), pain relief (Lechtzin et al, 2010) and enhanced neural connections in the medial prefrontal cortex of the brain (Hunter et al, 2010). This study has shown the percentage stating they are more relaxed after visiting the green space is closely associated with perceived tranquillity.…”
Section: Predicted Ratings and Adjustmentsmentioning
confidence: 61%
“…These are precisely the features that characterise natural surroundings. Earlier studies have shown a link between natural surroundings and the reduction of stress (Ulrich et al, 1991), recovery from surgical interventions (Ulrich, 1984), pain relief (Lechtzin et al, 2010) and enhanced neural connections in the medial prefrontal cortex of the brain (Hunter et al, 2010). This study has shown the percentage stating they are more relaxed after visiting the green space is closely associated with perceived tranquillity.…”
Section: Predicted Ratings and Adjustmentsmentioning
confidence: 61%
“…However, our green spaces and watersides can be a refuge from the din of town life and these environments provide shelter for wildlife and bird song and water sounds may be heard. Numerous studies have shown a link between such tranquil environments and stress reduction, well-being, longevity, pain relief and how the brain processes auditory signals [2][3][4][5][6][7]. It is therefore important to consider its protection, enhancement and promotion in a variety of urban landscapes and especially where visitors are likely to seek relief from the stresses and strains of everyday life.…”
mentioning
confidence: 99%
“…Park and Mattson 15 demonstrated that surgical patients exposed to indoor plants in their hospital room showed more positive physiologic responses, reported significantly lower levels of anxiety and fatigue, and higher satisfaction about their room, compared to a control condition. Recently, Lechtzin and colleagues 16 showed that patients undergoing bone marrow aspiration and biopsy experienced reduced pain when watching a nature scene (but only after controlling for different operators). Despite these positive findings, a recent literature review concluded that the effects of exposure to indoor plants on psychologic benefits are at best mixed.…”
mentioning
confidence: 99%